INTERFERENCE OF ABORTION LAW ON THE RELATIONSHIP BETWEEN ECONOMIC DEVELOPMENT AND FERTILITY RATE OF WOMEN - Ghosh, Dona; Bhattacharyya, Chandril (Indian Journal of Finance and Banking, 2022)
The last few decades have seen unprecedented economic growth and fertility decline. However, the relationship between economic development and fertility rate varies across the countries due to country-specific characteristics. There are two schools of thought in the existing literature: the first holds that women's fertility declines with economic development, which happens in tandem with industrialization, while the second holds that fertility rises with economic development because it encourages early marriage, coupled with, increase in economic security. However, there is a dearth of information in the literature regarding how various birth control regulatory systems affect the connection between fertility and economic development. Therefore, the present study attempts to analyze the relationship between birthrate and growth of GDP per capita in 182 nations (using panel data from 1990 to 2012). The study has three major findings. First, it implies the U-shaped association between economic progress and fertility rate is not universal. Second, the law affects women's fertility. More abortion restrictions boost a woman's fertility. Finally, cultural influences like previous periods' fertility rates affect the current period's fertility, indicating an intertemporal link. The study contributes to the in-depth understanding of the determinants of fertility rate. It identified how the abortion law influence the relationship between economic development and fertility rate. The findings can help in designing the fertility control measures, based on a country’s status of economic development.JEL Classification Codes: K42, O1, J13.